Knowing Your Product Costs: A Primer for Farmers and Food Entrepreneurs - Kevin Athearn; Mark Yarick; Natasha Parks (EDIS)
This publication provides a basic introduction to product costing for farm businesses and food processing enterprises. It describes cost concepts, provides product costing examples, and briefly discusses software tools that can assist with cost analysis. The publication is intended to help farmers and food entrepreneurs understand product costing concepts and do their own cost calculations to assist with business decisions.